2021
DOI: 10.1002/ctm2.319
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering DSC2 arrhythmogenic cardiomyopathy electrical instability: From ion channels to ECG and tailored drug therapy

Abstract: Thorough analysis of hiPSC-CM derived from a DSC2 patient, zebrafish and patient cohort, we identified abnormal repolarization dynamicity, prompting the discovery of a short QT interval in some ACM patients. By normalizing the increased repolarization reserve of ACM myocytes, class 3 AADs are likely to be the drugs of first choice for DSC2 patients. These findings may encourage randomized trials to evaluate class 3 antiarrhythmic drugs, alone or in combination with class I medications in ACM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 50 publications
3
44
0
1
Order By: Relevance
“…We derived hiPSCs from the same ACM-DSC2 patient, differentiated them into hiPSC-CMs, and cultured them for 60 days as described. 3 We found a similar higher expression of PPARγ and of two pro-adipogenic target genes, perilipin and adiponectin, in DSC2-hiPSC-CMs versus control-hiPSC-CMs (Figure 1A-C). Despite lower expression, the pro-cardiac myosin light chain 2 ventricular (MLC2v) validated the cardiomyocyte phenotype of DSC2-hiPSC-CMs (Figure 1D).…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…We derived hiPSCs from the same ACM-DSC2 patient, differentiated them into hiPSC-CMs, and cultured them for 60 days as described. 3 We found a similar higher expression of PPARγ and of two pro-adipogenic target genes, perilipin and adiponectin, in DSC2-hiPSC-CMs versus control-hiPSC-CMs (Figure 1A-C). Despite lower expression, the pro-cardiac myosin light chain 2 ventricular (MLC2v) validated the cardiomyocyte phenotype of DSC2-hiPSC-CMs (Figure 1D).…”
mentioning
confidence: 56%
“…These modifications are risk factors for triggering arrhythmias independently of fibrofatty replacement of myocardial tissue. 3 We now show that PPARγ, a master regulator of the cardiomyocytes transdifferentiation into adipocytes, is critical early in the pro-arrhythmogenic pathogenesis in ACM-DSC2-hiPSC-CMs.Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analysis of heart samples revealed a higher PPARγ gene expression level in the ACM-heart bearing the DSC2 mutation than in the control heart (Figure S1). We derived hiPSCs from the same ACM-DSC2 patient, differentiated them into hiPSC-CMs, and cultured them for 60 days as described.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…We demonstrated that the duration of the cellular action potential had shortened, and that the pacing rate had lost some of its ability to adapt. 4 Most patients with ACM exhibit a right ventricular parietal block, a reduced QRS amplitude, an epsilon wave, and an inversion in the T wave in V 1 –V 3 . However, the dynamicity of the QT or JT interval has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The possible ACM-associated mutations linked to conduction system impairments have been little, if at all, investigated. Moreau et al [35] studied an ACM patient with a missense mutation (c.394C>T) in the DSC2 gene, using a zebrafish DSC2 model system. The DSC2 patient-derived pluripotent stem cells were reprogrammed and differentiated into cardiomyocytes, the human-induced pluripotent stem cells cardiomyocytes (hiPSC-CM).…”
Section: Geneticsmentioning
confidence: 99%